Bài làm
\(\frac{1}{3}+\frac{3}{4}-\left(-\frac{3}{5}\right)+\frac{1}{72}+\frac{2}{9}-\left(-\frac{1}{36}\right)+\frac{1}{15}\)
\(=\frac{1}{3}+\frac{3}{4}+\frac{3}{5}+\frac{1}{72}+\frac{2}{9}+\frac{1}{36}+\frac{1}{15}\)
\(=\left(\frac{1}{3}+\frac{3}{5}+\frac{1}{15}\right)+\left(\frac{1}{36}+\frac{3}{4}\right)+\left(\frac{1}{72}+\frac{2}{9}\right)\)
\(=\left(\frac{5}{15}+\frac{9}{15}+\frac{1}{15}\right)+\left(\frac{1}{36}+\frac{27}{36}\right)+\left(\frac{16}{72}+\frac{1}{72}\right)\)
\(=1+\frac{28}{36}+\frac{18}{72}\)
\(=\frac{36}{36}+\frac{28}{36}+\frac{9}{36}\)
\(=\frac{73}{36}\)
~ Không chắc có đúng hay không nx. ~
# Học tốt #
Sửa đề :
\(\frac{1}{3}+\frac{3}{4}-\left[-\frac{3}{5}\right]+\frac{1}{72}+\frac{2}{9}-\frac{1}{36}+\frac{1}{15}\)
\(=\frac{1}{3}+\frac{3}{4}+\frac{3}{5}+\frac{1}{72}+\frac{2}{9}-\frac{1}{36}+\frac{1}{15}\)
\(=\left[\frac{1}{3}+\frac{3}{5}+\frac{1}{15}\right]-\left[\frac{3}{4}+\frac{2}{9}+\frac{1}{36}\right]+\frac{1}{72}\)
\(=\left[\frac{5}{15}+\frac{9}{15}+\frac{1}{15}\right]-\left[\frac{27}{36}+\frac{8}{36}+\frac{1}{36}\right]+\frac{1}{72}\)
\(=1-1+\frac{1}{72}=\frac{1}{72}\)